Adsorption, Desorption and Mobility of Amides in Soils - Rungsit Suwanketnikom; Ubonwan Kiatboonyarit (Agriculture and Natural Resources, 1990)
Experiments on adsorption, desorption and movement of diphenamid [ N, N-dimethyl-2, 2-diphenylacetamide ], metolachlor [ 2 chloro-N-(2-ethyl-6-methyl phenyl )-N-(2-methoxy-1-methyl-ethyl) acetamide ], napropamide [ 2-(-naptoxy)-N, N-diethyl propionamide ] and pretilachlor [ 2-chloro-2, 6 diethyl-N-( 2-propoxyethyl ) – acetanilide ] were conducted in four commonly occurring soils of Central Thailand. The soils were Bang Khen clay ( Bang Khen series ), Pak Chong clay loam, ( Pak Chong series ) Kamphaeng Saen loam ( Kamphaeng Saen series ) and Sattahip loamy sand ( Sattahip series ). Organic carbon contents of the soils by weight varied from 0.56 to 2.75 percent and clay fraction ranged from 5 to 57 percent. Freundlich adsorption isotherms and distribution coefficient exhibited that amides were adsorbed in the order napropamide > pretilachlor > metolachlor > diphenamid. Rf values indicated the order of herbicide movement to be pretilachlor > diphenamid > metolachlor > napropamide. However, very high rate of pretilachlor movement occurred only in Kamphaeng Saen loam and Sattahip loamy sand, Furthermore, very small fraction of pretilachlor was mobile but the large fraction remained at the site of application. All herbicides were desorbed in all soil types. It was demonstrated that diphenamid and metolachlor were sufficiently mobile in soils low in organic carbon and clay content and could cause possible loss of efficacy or they could accumulate in ground water.